2024
DOI: 10.3390/ijms25010587
|View full text |Cite
|
Sign up to set email alerts
|

Role of SLC7A11/xCT in Ovarian Cancer

Sonia Fantone,
Federica Piani,
Fabiola Olivieri
et al.

Abstract: Ovarian cancer is one of the most dangerous gynecologic cancers worldwide and has a high fatality rate due to diagnosis at an advanced stage of the disease as well as a high recurrence rate due to the occurrence of chemotherapy resistance. In fact, chemoresistance weakens the therapeutic effects, worsening the outcome of this pathology. Solute Carrier Family 7 Member 11 (SLC7A11, also known as xCT) is the functional subunit of the Xc− system, an anionic L-cystine/L-glutamate antiporter expressed on the cell su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 126 publications
(156 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, the effect of ATF4 on NRF2 is also mediated by a cystine/glutamate antiporter (i.e., SLC27A11) [30]. The role of the protein coded by SLC7A11 is not clear in mammary tissue; however, it has been implicated in the maintenance of intracellular glutathione levels and chemotherapeutic resistance in both ovarian [36] and lung cells [37]. Furthermore, an increase in the expression of amino acid transporters can benefit milk protein synthesis [38], although this amino acid transporter was the only one upregulated by SFN (see Supplementary File S1).…”
Section: Gene Targets Of Nrf2 In Mact Cellsmentioning
confidence: 99%
“…Interestingly, the effect of ATF4 on NRF2 is also mediated by a cystine/glutamate antiporter (i.e., SLC27A11) [30]. The role of the protein coded by SLC7A11 is not clear in mammary tissue; however, it has been implicated in the maintenance of intracellular glutathione levels and chemotherapeutic resistance in both ovarian [36] and lung cells [37]. Furthermore, an increase in the expression of amino acid transporters can benefit milk protein synthesis [38], although this amino acid transporter was the only one upregulated by SFN (see Supplementary File S1).…”
Section: Gene Targets Of Nrf2 In Mact Cellsmentioning
confidence: 99%
“…Changes in the levels of GSH, the essential coenzyme of GPX4, directly affect the enzyme’s ability to reduce lipid hydroperoxides, thus influencing its antioxidant capacity and the regulation of ferroptosis ( Endale and Mengstie, 2023 ). Therefore, the overexpression of SLC7A11 in ovarian cancer cells enhances GPX4 activity by increasing GSH levels, which assists cells in resisting ferroptosis and promotes cancer cell proliferation, invasion, and chemoresistance ( Fantone et al, 2024 ). Qin et al (2023) also reported that SLC7A11 protein levels were significantly greater in cisplatin-resistant A2780/DDP and SKOV3/DDP ovarian cancer cell lines than in their cisplatin-sensitive counterparts.…”
Section: Reversing Chemoresistance In Gynecological Malignancies Thro...mentioning
confidence: 99%
“…Serous ovarian cancer, divided into low-grade and high-grade carcinoma, is one of the most frequently diagnosed ovarian epithelial carcinomas [2]. The biological behavior of high-grade serous ovarian cancer, such as rapid growth, high aggressiveness, and chemoresistance, often leads to poor prognosis for patient survival [2]; thus, new therapeutic targets for ovarian cancer treatment are needed [3]. Currently, keen attention is paid to the discovery of rapid screening tests for ovarian cancer and the development of new targeted therapies.…”
Section: Introductionmentioning
confidence: 99%